Contribuições do ensino de libras nos cursos de licenciatura - Pedroni, Vinícius Hidalgo (2021)
The present dissertation reflects the continuation of researches interested in understanding the relationship difficulties between deaf and hearing cultures. These difficulties, observed not only throughout the history of education, but throughout the history of the deaf. It is notorious the segregation of the deaf living in small communities, in the most varied spaces of socialization. In this sense, the research in question set out to investigate qualitatively what are the contributions that the mandatory teaching of Brazilian Sign Language in different degree courses has been bringing to the reduction or perhaps even a possible elimination of barriers that prevent the full coexistence between these two groups: deaf and hearing. To this end, we present in the text a review of the main theorists related to the education of the deaf, culture and deaf identity and sign language such as Quadros (2013), Perlin (2003) and Felipe (2001). We also contextualize here some aspects of Libras teaching to listeners, especially in teacher training courses, we characterize the courses researched at the Arraias and Porto Nacional campuses, at UFT - Federal University of Tocantins and, finalize the dissertation, we present the methodology research and the analysis of the results found, which showed us difficulties in learning Libras due to the lack of conversation practice during classes, the insufficient amount of class hours to study the discipline and the absence of specific methodology for its teaching . These results revealed an incomplete ability of the future teacher to use sign language to better serve a student with deafness.